Flows of Reactive Fluids - Prud'homme, Roger; SpringerLink (Online service) (Boston : Birkhäuser Boston, 2010)
The modeling of reactive flows has progressed mainly with advances in aerospace, which gave birth to a new science called aerothermochemistry, as well as through developments in chemical and process engineering. The methods employed, the phenomena investigated, and the aims of modeling differ for each field; however, in all cases, the results obtained have considerably enriched the working knowledge of reactive flows. This work examines basic concepts and methods necessary to study reactive flows and transfer phenomena in areas such as fluid mechanics, thermodynamics, and chemistry. Specific topics covered include: * Equations of state * Transfer phenomena and chemical kinetics * Balance equations of reactive flows * Dimensionless numbers and similarity * Chemical reactors * Coupled phenomena * Turbulent flow concepts * Boundary layers and fluid layers * Reactive and nonreactive waves * Interface phenomena * Multiphase flow concepts The book presents tools of interest to graduate students, researchers in mathematical physics, and engineers who wish to investigate problems of reactive flows. Portions of the text may be used in courses on the physics of liquids or in seminars on mechanics.
Equations of State -- Transfer Phenomena and Chemical Kinetics -- Balance Equations for Reactive Flows -- Dimensionless Numbers and Similarity -- Chemical Reactors -- Coupled Phenomena -- Turbulent Flow Concepts -- Boundary Layers and Fluid Layers -- Reactive and Nonreactive Waves -- Interface Phenomena -- Multiphase Flow Concepts.
Keywords: Engineering; Thermodynamics; Hydraulic engineering; Engineering; Engineering Fluid Dynamics; Mathematical Modeling and Industrial Mathematics; Engineering Thermodynamics, Heat and Mass Transfer; Classical Continuum Physics; Fluid- and Aerodynamics; Thermodynamics